Photoadaptation in neurospora by competitive Iínteraction of activating and inhibitory LOV Domains - Malzahn, Erik; Ciprianidis, Stilianos; Káldi, Krisztina; Schafmeier, Tobias; Brunner, Michael (Cell, 2010)
Light responses and photoadaptation of Neurospora depend on the photosensory light-oxygen-voltage (LOV) domains of the circadian transcription factor White Collar Complex (WCC) and its negative regulator VIVID (VVD). We found that light triggers LOV-mediated dimerization of the WCC. The activated WCC induces expression of VVD, which then disrupts and inactivates the WCC homodimers by the competitive formation of WCC-VVD heterodimers, leading to photoadaptation. During the day, expression levels of VVD correlate with light intensity, allowing photoadaptation over several orders of magnitude. At night, previously synthesized VVD serves as a molecular memory of the brightness of the preceding day and suppresses responses to light cues of lower intensity. We show that VVD is essential to discriminate between day and night, even in naturally ambiguous photoperiods with moonlight.
Gesehen am 03.05.2023